Synthesis and Oxidation ofCobalt(II) Pheophytin-α Complex - Ezekiel D. Dikio; David A. Isabirye (E-Journal of Chemistry)
The mechanism of oxidation of natural pheophytin-a incorporated with cobalt as the central metal ion has been investigated. Natural pheophytin-aextracted from spinach was metallated with cobalt(II) to form the complex, cobalt(II) pheophytin-α [Cophe]. The complex was characterized by Ultraviolet and Visible, Fourier Transform Infrared and Electrospray ion Mass Spectroscopy. The synthesis of cobalt(II) pheophytin-a was carried out and the effect of the substitution on the chlorophyll macrocycle was studied by the reaction of hexaaquachromium(III) cation. The presence of cobalt as the central metal ion increases the energies of the chlorophyll main absorption transitions. The oxidation of the cobalt(II) pheophytin-α, [Cophe] by hexaaquachromium(III) cation in dilute hydrochloric acid has been studied and found to follow first-order kinetics. Rate constants for the oxidation reaction at 313, 322.8 and 332.9 K were found to be 5.4×10-5, 1.8×10-4 and 5.9×10-4/s respectively. An outer-sphere mechanism has been proposed for the oxidation of cobalt(II) pheophytin-α.